Analisis faktor risiko kejadian infeksi saluran pernapasan akut di Abiansemal Kabupaten Badung tahun 2018 - Ni Made Marwati; I Wayan Sali; I Made Bulda Mahayana; I Gusti Ayu Made Aryasih (DiscoverSys Inc., 2022)
Background: Acute Respiratory Tract Infections (ARTI) is one of the main causes of patient visits to the public health center (40%-60%) and hospital (15%-30%). The purpose of this study was to determine various risk factors that influence the incidence of ARTI in Abiansemal in 2018.Methods: This research was an observational study using a case-control research design by looking for various relationships of risk factors on the incidence of ARTI. The case group consists of patients diagnosed with ARTI and the control group were those who were not diagnosed with ARTI. The independent variables in this study were room occupancy density, kitchen room ventilation, smoking habits of parents, bedroom and living room ventilation, bedroom and living room light intensity, bedroom and living room air temperature, bedroom and living room, floor and wall humidity.Result: The bivariate analysis showed that the risk factors for the incidence of ARTI were room occupancy density with a value of ?=0.05 (p=0.000, OR=28.444), smoking habits of the parents (p=0.000, OR=20.000), bedroom ventilation (p=0.003, OR=10.500), bedroom light intensity (p=0,000, OR=67,500), living room light intensity (p=0.001, OR=14.063), bedroom air temperature (p=0.002, OR=14.571), bedroom air humidity (p=0,000, OR=20,000).Conclusion: There were seven factors that were significantly associated with the incidence of ARTI in Abiansemal includeing room occupancy density, smoking habits of the parents, bedroom ventilation, bedroom light intensity, living room light intensity, bedroom air temperature, and bedroom air humidity. Latar Belakang: Infeksi Saluran Pernafasan Akut (ISPA) merupakan salah satu penyebab utama kunjungan pasien ke Puskesmas (40%-60%) dan rumah sakit (15%-30%). Tujuan dari penelitian ini adalah untuk mengetahui berbagai faktor risiko yang mempengaruhi kejadian ISPA di Abiansemal tahun 2018.Metode: Penelitian ini merupakan penelitian observasional dengan desain penelitian kasus kontrol dengan mencari berbagai hubungan faktor risiko terhadap kejadian ISPA. Kelompok kasus terdiri dari pasien yang terdiagnosis ISPA dan kelompok kontrol adalah mereka yang tidak terdiagnosis ISPA. Variabel bebas dalam penelitian ini adalah kepadatan hunian kamar, ventilasi ruang dapur, kebiasaan merokok orang tua, ventilasi kamar tidur dan ruang tamu, intensitas cahaya kamar tidur dan ruang tamu, suhu udara kamar tidur dan ruang tamu, kamar tidur dan ruang tamu, kelembaban lantai dan dinding.Hasil: Analisis bivariat menunjukkan bahwa faktor risiko kejadian ISPA adalah kepadatan hunian kamar dengan nilai 0,05 (p=0,000, OR=28,444), kebiasaan merokok orang tua (p=0,000, OR=20,000), ventilasi kamar tidur (p=0,003, OR=10,500), intensitas cahaya kamar tidur (p=0,000, OR=67,500), intensitas cahaya ruang tamu (p=0,001, OR=14,063), suhu udara kamar tidur (p=0,002, OR= 14,571), kelembaban udara kamar tidur (p=0,000, OR=20,000).Kesimpulan: Terdapat tujuh faktor yang berhubungan signifikan dengan kejadian ISPA di Abiansemal meliputi kepadatan hunian kamar, kebiasaan merokok orang tua, ventilasi kamar tidur, intensitas cahaya kamar tidur, intensitas cahaya ruang tamu, suhu udara kamar tidur, dan kelembaban udara kamar tidur.